Virulence of Bursaphelenchus mucronatus to pine seedlings and trees under field cownditions. Issue 6 (21st June 2016) - Zhou, L. F.; Chen, F. M.; Wang, J. C.; Pan, H. Y.; Ye, J. R.
Summary: Bursaphelenchus mucronatus is a parasitic nematode of pine that is widely distributed in the natural pine forests of Asia and Europe. It has a very similar morphology and biology to that of Bursaphelenchus xylophilus, the causal agent of pine wilt disease, but has generally been considered to be non‐pathogenic to pine. However, in some provinces of China, B. mucronatus has been isolated from dead pine trees rather than B. xylophilus . Previous studies have shown that B. mucronatus can induce the death of pine seedlings under glasshouse conditions. To investigate the virulence of B. mucronatus, 2‐year‐old seedlings of Pinus massoniana and Pinus elliottii were inoculated with one of six isolates of B. mucronatus under field conditions in April 2014 and their condition was monitored over a year. The virulence of the six B. mucronatus isolates differed on the three host species: P. elliottii seedling mortality ranged from zero to six of the 18 inoculated seedlings, whereas P. massoniana seedling mortality ranged from four to 12 of the 18 inoculated seedlings. Three B. mucronatus isolates that appeared to cause different levels of mortality among the seedlings were used to inoculate 12‐year‐old Pinus thunbergii trees in August 2014. The trees were monitored for a year, during which time between 4 and 12 of the 18 inoculated trees in each treatment wilted and died. The average monthly temperature during the test period appeared to be similar to that of the historical average in the test areas; however, both study sites experienced above‐average rainfall. This study demonstrated that B. mucronatus has potential virulence on pine trees and provided experimental evidence that high temperatures or drought stress is not essential for the virulence of B. mucronatus .